2016
DOI: 10.1287/msom.2015.0570
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting Strategic Purchase Deferrals: The Impact of Online Retailers’ Return Policy Decisions

Abstract: Online shoppers value lenient return policies as they are unable to assess whether products match their expectations. We study how consumers’ discount-seeking purchase deferrals affect online retailers’ return policy choices. Lenient returns may induce higher full-price sales by limiting consumer regret, while signaling clearance unavailability risk. Contrasting earlier research that concluded a monopolist must set the refund at the clearance price when strategic consumers were overlooked, we find that an opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(57 citation statements)
references
References 34 publications
1
54
0
2
Order By: Relevance
“…In this subsection, the retailer offers offline return service and chooses not to enter the platform. As we all know, returned products have less value than new products, that is, the salvage value of returned product v is less than the product production cost c ; a similar assumption can be found in Altug and Aydinliyim (). Considering return loss, the retailer's profit function can be presented as follows: maxRNYfalse(psfalse)=DsNYfalse[αs(psc)+(1αs)(vc)hrfalse].…”
Section: Problem Descriptionsupporting
confidence: 52%
See 1 more Smart Citation
“…In this subsection, the retailer offers offline return service and chooses not to enter the platform. As we all know, returned products have less value than new products, that is, the salvage value of returned product v is less than the product production cost c ; a similar assumption can be found in Altug and Aydinliyim (). Considering return loss, the retailer's profit function can be presented as follows: maxRNYfalse(psfalse)=DsNYfalse[αs(psc)+(1αs)(vc)hrfalse].…”
Section: Problem Descriptionsupporting
confidence: 52%
“…Then Mukhopadhyay and Setaputra () further investigated optimal return strategies of online retailers. Moreover, some scholars studied online return strategies under different scenarios, such as the impact of consumer action of waiting for product discounts on optimal return strategies (Altug and Aydinliyim, ), firms’ optimal shipping cost and return service fee in the context of no‐reason return policy (Hua et al., ), the impact of consumer returns of optimal channel choice of manufacturers (Letizia et al. ), and optimal offline showroom strategy while considering consumer returns (Li, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bower and Maxham [25] used two surveys and actual customer spending dates to indicate normative assumptions and the long-term consequences of fee and free returns and presented the idea that online retailers should offer either a free online return policy or a minimum fee return policy if they can determine consumers' reactions to fee returns. Altug and Aydinliyim [26] studied how consumers' discount-seeking purchase deferrals affect the return policy of online retailers and found that retailers in some conditions can gain a competitive advantage when selling to strategic consumers. Sahoo et al [27] explored the impact of online product reviews on the optimal online return strategy and showed that unbiased online reviews benefit consumers and that biasing reviews upwards results in more returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies show that a product's salvage value is a critical determinant of a retailer's optimal return policy choices. In particular, these studies find that retailers with more efficient salvaging options can offer more lenient policies (Altug & Aydinliyim, 2016;Davis et al, 1995;Su, 2009). Shulman et al (2010) focus on reverse channel design for salvaging.…”
Section: Chen Et Al (2018)mentioning
confidence: 99%